Wanprestasi dalam Kontrak Sewa Menyewa - Nailis Nurul Hikmah; Alifaya Najla Abdini; Jasmina Fahira Rizkiyanti; Putri Na'ilah Zulfah; M. Shidqon Prabowo (Universitas Wahid Hasyim, 2024)
This research is intended to find out the misconduct on the law of alliance that occurs in a lease contract. The investigation was conducted in a jurisprudential manner to analyse the existence of misconduct by creditors and debtors in accordance with the decision No. 56/Pdt.G/2020/PN Sdw, as the claimant is a creditor and the claimed is a debtor. The Yuridist approach is intended as an attempt to bring the problems studied closer to the normative nature of law. Through this juridical-normative approach it is possible to know how the implementation or application of formal law in a legal event occurs with the aim of ensuring its application has been in accordance with the provisions of the law. The discussion in this study covers the understanding of alliance and non-performance according to the Perdata Code as well as the legal consequences arising from a non -performance. In addition, we will discuss the misconduct in a legal event, namely the rental lease, contained in the decision No. 56/Pdt.G/2020/PN Sdw. The conclusion of this study is that non-performance can be interpreted as non-fulfilment of obligations by the debtor to the creditor in an alliance